Characterization of the complete chloroplast genome of Elymus sibiricus Linn (Gramineae). Issue 1 (2nd January 2019) - Ding, Chengxiang; Dong, Quanmin; Yang, Xiaoxia; Zhang, Chunping; Chu, Hui
Abstract: The complete chloroplast genome from Elymus sibiricus Linn, an important forage grass of the Gramineae, is determined in this study. The whole chloroplast genome sequence of E. sibiricus Linn has been characterized by Illumina pair-end sequencing. The circular genome is 135, 074 bp long, containing a large single copy region (LSC) of 80, 681 bp and a small single copy region (SSC) of 12, 767 bp, which are separated by a pair of 20, 813 bp inverted repeat regions (IRs). It encodes a total of 142 genes, including 86 protein-coding genes (81 PCG species), 48 tRNA genes (30 tRNA species) and eight ribosomal RNA genes (four rRNA species). The most of gene species occur as a single copy, while 16 gene species occur in double copies. The overall A + T content of is 61.7%, while the corresponding values of the LSC, SSC and IR regions are 63.6%, 67.8% and 56.0%, respectively. Phylogenetic analysis suggested that E. sibiricus Linn was relatively close to Connorochloa tenuis compared with species of other generain Gramineae among the species analyzed. This complete chloroplast genome will provide valuable insight into conservation and exploitation efforts for this species as well as useful resources for studying the Gramineae phylogeny.